Chemical Analysis of Effectiveness of Integrated Practicum Learning in Class XII-IPA SMA on The Implementation of Curriculum 2013 in Medan - Bajoka Nainggolan (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstract, Execution learning integrated chemical lab on the implementation of the curriculum in 2013 focused on the development of the balance of the ability to form good human (soft skills), with life skills appropriately (hardskills) on the competence of the knowledge, skills, and spiritual attitudes through learning is planned and effective, do scientific approach (scientific approach), through the competence of attitudes, knowledge, and skills to observe, ask questions, reason, analyze, innovate and communicate appropriately and effectively. The effectiveness of the implementation of the integrated chemical lab learning is defined as the thoroughness and success achieved after the implementation of learning. For it to do research with the aim to find out how the effectiveness of the integrated chemical lab learning in class XII-IPA on curriculum implementation in 2013 in SMA Medan in 2016. Samples were taken from the population as much as 5 purposiv chemistry teacher class XII-Science, 15th graders XII-IPA, and laboratory 5 of 5 SMA. Data obtained through questionnaires, interviews, and observations based on the frequency distribution persentatif processed and analyzed descriptively qualitative. The results of the questionnaire obtained a majority (60%) and chemistry teacher (66.67%) students less effective category. The results of the interview (60%) chemistry teacher, (53.33%) sisiwa, and (80%) laboratory majority of categories less effective in teaching practices integrated chemical lab. Results observation documentation, laboratory facilities and infrastructure gained less support and less effective category. Of the 10 topics that should be practiced practicum students, the results obtained; two high schools implement complete practicum title 5 (50%), a high school title completed executing 3 (30%), and two high schools did not carry out a practicum (completeness 0%). From the results it can be concluded that the implementation of the integrated chemical lab learning in class XII IPA SMA-on curriculum implementation in 2013 in the city of Medan category less effective.Keywords: effectiveness, implementation of integrated chemical lab learning, curriculum 2013